"Setara Daring" Learning Managementon Learning Results In Package C at PKBM Lestari Banyuwangi - Ema Rosita; Muhammad Irfan Hilmi; Niswatul Imsiyah (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
In the learning program, the “seTARA daring” application has been provided by the government to make it easier to carry out equality learning activities. At PKBM Lestari, they chose to do bold learning using the “seTARA daring” learning media application and using the home study method considering that the conditions of the students and PKBM were quite adequate. This study aims to find out how the management of learning “seTARA daring” is brave for the learning outcomes of Package C at PKBM Lestari Banyuwangi. This type of research is a qualitative with a descriptive method. The data sources in this study consist of research informants, namely tutors and learners package C. The data collection techniques used were observation, interviews, and documentation with data analysis used, namely data reduction, data presentation, and conclusions. Online equivalent management of learning outcomes Package C at PKBM Lestari Banyuwangi starting from planning, implementing, and evaluating learning carried out by tutors has been going well, namely the tutor has prepared material from modules and learning materials from youtube videos, methods, media, to the facilities and infrastructure needed during the brave learning process. The implementation of learning is carried out by utilizing digital technology such as mobile phones, via whatsapp groups, and the seTARA application. In the implementation of learning, the methods used are flipped classroom, lectures, and discussions